2021
DOI: 10.7717/peerj.10778
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of full-length nanopore 16S sequencing for detection of pathogens in microbial keratitis

Abstract: Background Microbial keratitis is a leading cause of preventable blindness worldwide. Conventional sampling and culture techniques are time-consuming, with over 40% of cases being culture-negative. Nanopore sequencing technology is portable and capable of generating long sequencing reads in real-time. The aim of this study is to evaluate the potential of nanopore sequencing directly from clinical samples for the diagnosis of bacterial microbial keratitis. Methods Using full-length 16S rRNA amplicon sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 77 publications
(94 reference statements)
1
25
0
Order By: Relevance
“…With the advancement of HTS technology, we are gaining increasing information on genes, transcripts, and non-coding RNAs (such as miRNA) [ 43 , 59 , 62 ]. The recent full-length nanopore 16S sequencing technology has the advantages of portability, low cost, and rapid sequencing [ 84 ]. It is increasingly used in the etiological diagnosis of various eye diseases and has also contributed greatly to exploring the normal microbiota that maintains ocular surface homeostasis [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of HTS technology, we are gaining increasing information on genes, transcripts, and non-coding RNAs (such as miRNA) [ 43 , 59 , 62 ]. The recent full-length nanopore 16S sequencing technology has the advantages of portability, low cost, and rapid sequencing [ 84 ]. It is increasingly used in the etiological diagnosis of various eye diseases and has also contributed greatly to exploring the normal microbiota that maintains ocular surface homeostasis [ 39 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low et al reported 16S rRNA gene analysis using a portable nanopore sequencer in two cases of keratitis 30. Jun et al also used a nanopore sequencer in eight cases of endophthalmitis 31.…”
Section: Discussionmentioning
confidence: 99%
“…Low et al reported 16S rRNA gene analysis using a portable nanopore sequencer in two cases of keratitis. 30 Jun et al also used a nanopore sequencer in eight cases of endophthalmitis. 31 Low et al reported the advantages of gene analysis using MinIONin detecting causative organisms after administering antimicrobial eye drops.…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA gene sequence is 1,550 bp long, and it is composed of nine variable regions (V1-V9) interspaced in more conserved regions. By amplifying the 16S rRNA region with PCR, the background host contamination encountered in routing culturing techniques is reduced significantly [98].…”
Section: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…Second-generation platforms (Illumina HiSeq 2500), although able to generate high sequence throughput data in a single reaction, they only sequenced part of the 16S gene [94,103,104]. Current third-generation platforms use nanopore sequencing technology directly from clinical samples to diagnose bacterial keratitis in real time and with higher accuracy [98].…”
Section: Next-generation Sequencing (Ngs)mentioning
confidence: 99%